The Role of Dopamine in the Context of Aversive Stimuli with Particular Reference to Acoustically Signaled Avoidance Learning - Ilango, Anton; Shumake, Jason; Wetzel, Wolfram; Scheich, Henning; Ohl, Frank W. (Frontiers in Neuroscience, 2012)
Learning from punishment is a powerful means for behavioral adaptation with high relevance for various mechanisms of self-protection. Several studies have explored the contribution of released dopamine (DA) or responses of DA neurons on reward seeking using rewards such as food, water, and sex. Phasic DA signals evoked by rewards or conditioned reward predictors are well documented, as are modulations of these signals by such parameters as reward magnitude, probability, and deviation of actually occurring from expected rewards. Less attention has been paid to DA neuron firing and DA release in response to aversive stimuli, and the prediction and avoidance of punishment. In this review, we first focus on DA changes in response to aversive stimuli as measured by microdialysis and voltammetry followed by the change in electrophysiological signatures by aversive stimuli and fearful events. We subsequently focus on the role of DA and effect of DA manipulations on signaled avoidance learning, which consists of learning the significance of a warning cue through Pavlovian associations and the execution of an instrumental avoidance response. We present a coherent framework utilizing the data on microdialysis, voltammetry, electrophysiological recording, electrical brain stimulation and behavioral analysis. We end by outlining current gaps in the literature and proposing future directions aimed at incorporating technical and conceptual progress to understand the involvement of reward circuit on punishment based decisions.